Study of outcome of type 1 interlay tympanoplasty - Mehta, Shailee; Bhastekar, Nifla (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: The aim of this study is to assess the success rate of interlay tympanoplasty and its related complications. Methods: This study was carried out in the department of otorhinolaryngology and head and neck surgery, GMERS medical college and hospital, Sola, Ahmedabad, Gujarat. In this observational study, 50 patients aged between 20-58 years with chronic otitis media were selected. Tuning fork test, pure tone audiogram, HRCT temporal bone, hemogram, anaesthesia fitness was done in all patients. Results: All patients underwent type 1 interlay tympanoplasty with success rate of 96 % (48 cases out of 50). Conclusions: Patients were followed up for a period of 2 months at which point they were assessed both endoscopically and from an audiological point of view.